Oxygen uptake, heart rate and activities of locomotor muscles during a critical swimming speed protocol in the gilthead sea bream Sparus aurata. Issue 3 (9th December 2020) - Hachim, Mouniboudine; Rouyer, Tristan; Dutto, Gilbert; Kerzerho, Vincent; Bernard, Serge; Bourjea, Jérôme; McKenzie, David J.
Abstract: Oxygen uptake, heart rate and contraction frequencies of slow oxidative (SO) and fast glycolytic (FG) muscle were measured simultaneously in gilthead seabream Sparus aurata submitted to stepwise increases in current speed in a swimming respirometer. Variation in oxygen uptake was closely related to variation in heart rate, over initial steps these rose in concert with an increase in contraction frequency of SO muscle. There was an asymptote in oxygen uptake and heart rate at high speeds that reflected a transition from exclusive use of aerobic SO muscle to a combination of SO and anaerobic FG muscle, and which preceded fatigue.